PEMANFAATAN LIMBAH UBI KAYU DARI SISA PENGOLAHAN TEPUNG TAPIOKA DI KECAMATAN MARGOYOSO KABUPATEN PATI MENJADI BAHAN ADSORBEN UNTUK PENJERNIH AIR - Karunawan, Jotti; Wati, Annisa Lidia; Rahmawati, Ita; Sulhadi, Sulhadi; Priyanto, Aan; Aji, Mahardika Prasetya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
One of the central cassava production is located in Pati Regency Central Java. The high production of cassava is supported by cassava post-harvest and process it into tapioca flour. However, the problem arises during the production of tapioca flour from cassava. Waste materials which are produced from tapioca flour production pollute the environment. Charcoal (carbon material) has been produced from tapioca waste material production through pyrolysis process. The carbon performance is tested by analyzing its absorbance toward methylene blue solutions. The carbon performance testing shows that the absorption intensity of methylene blue decreased. This result indicates the absorption of methylene blue by carbon. The descent rate of methylene blue intensity is correspond to tho the addition of carbon mass. Carbon from cassava waste is effective as absorbent to reduce methylene blue textile waste. Keywords: Waste, Cassava, Pati district.